Zooplankton species composition, abundance and diversity in lakes with different trophic status - Ahmad Dini, Umi Wahidah (2017)
Zooplanktons are microscopic aquatic organisms that have short life cycle and rapid reproduction rate which enable them to respond quickly to environmental changes. Their distributions are influenced by various abiotic and biotic factors. Elevated nutrient input into water bodies leads to eutrophication, which would in turn affect the zooplankton distribution. This study was conducted to evaluate the zooplankton species composition, abundance and diversity in lakes with different trophic status in order to relate the changes in zooplankton community with different trophic levels, and to identify potential zooplankton species as bioindicators. Bimonthly sampling was carried out in Subang, Putrajaya and Sembrong lakes at three stations in each lake, from April 2015 to February 2016. Duplicate zooplankton samples were collected from each station with a 60-μm mesh net using vertical hauls and preserved with 10% buffered formalin for identification and enumeration. Physicochemical parameters were measured in situ. Nutrient analyses and chlorophyll a determination were performed following the standard method. Conductivity, pH, total dissolved solid (TDS), turbidity, total phosphorus (TP), total nitrogen (TN) and chlorophyll a were significantly higher (p < 0.05) in Sembrong lake. Based on the Carlson Trophic Status Index (CTSI), Sembrong lake was classified as hypereutrophic lake, Putrajaya lake as meso-eutrophic lake and Subang lake as mesotrophic lake. The highest rotifer species was recorded in Putrajaya lake with 28 species. The highest (p < 0.05) rotifer density was observed in Putrajaya lake with a total mean density of 239.4 ± 30.3 ind. l-1. Rotifer assemblage of Sembrong lake was dominated by Brachionus forficula (23.3 %) and B. calyciflorus (18.0 %). In Putrajaya lake, the major species was Keratella cochlearis which contributed to 38.0 %. Subang lake showed a clear domination of P. libera contributing to 76.1 %. Rotifer diversity was highest in Sembrong lake with H' = 1.9 ± 0.0. The abundance of Brachionus and Keratella were related to the eutrophic condition. Ptygura libera seemed to be associated to waters with relatively high transparency. The highest microcrustacean species was recorded in Putrajaya lake with eight species. However, the highest (p < 0.05) microcrustacean density was observed in Sembrong lake with a total mean density of 293.7 ± 60.7 ind. l-1. Microcrustacean species assemblage of Sembrong lake was dominated by Ceriodaphnia cornuta with 66.0 %. In Putrajaya lake, the dominant species was Bosmina longirostris which made up 46.8 %. Meanwhile, in Subang lake Thermocyclops crassus was the dominant species contributing to 74.0 %. The highest diversity of microcrustacean was observed in Putrajaya lake with H' = 1.3 ± 0.0. The abundance of small size cladocerans such as C. cornuta and B. longirostris were related to the eutrophic conditions of the lakes. This study illustrated that the zooplankton composition and abundance were related to the environmental characteristics and trophic status of lakes.